Impact of malnutrition and nutrition support in hospitalised patients with inflammatory bowel disease. Issue 8 (13th January 2023) - Dua, Anoushka; Corson, Melissa; Sauk, Jenny S.; Jaffe, Nancee; Limketkai, Berkeley N.
Summary: Background: Malnutrition is prevalent in patients with inflammatory bowel disease (IBD) and has been associated with worse clinical outcomes. Aims: This observational study examines trends in protein‐calorie malnutrition (PCM) amongst hospitalised IBD and non‐IBD patients, and the association between (1) malnutrition and (2) nutrition support and hospitalisation outcomes. Methods: We queried the Nationwide Readmissions Database from 2010 to 2018 for hospitalisations with and without IBD. Amongst patients with IBD and concurrent PCM, we identified those who received nutrition support. Multivariable Cox proportional hazards and Kaplan‐Meier analyses evaluated the associations between PCM and nutrition support and readmission and mortality. Multiple linear regression described the association between compared variables and length of stay (LOS) and total hospitalisation costs. Results: This study included 1, 216, 033 patients (1, 820, 023 hospitalisations) with Crohn's disease (CD), 832, 931 patients (1, 089, 853 hospitalizations) with ulcerative colitis (UC) and 240, 488, 656 patients (321, 220, 427 hospitalisations) without IBD. Admitted IBD patients were 2.9–3.1 times more likely to have PCM than non‐IBD patients. IBD patients with PCM had a higher risk of readmission and mortality, as well as longer LOS and higher hospitalisation costs. Nutrition support (parenteral and enteral) was associated with a reduced risk of readmission, but higher mortality increased LOS and higher total hospitalisation costs. Conclusions: Malnutrition in hospitalised IBD patients remains an important contributor to readmission, mortality, LOS and healthcare costs. Providing nutrition support to IBD patients may reduce the risk of readmission. Further studies are needed to evaluate the role of nutrition support amongst hospitalised IBD patients to optimise disease and healthcare outcomes. Abstract :